Correction: One-step trapping of droplets and surface functionalization of sensors using gold-patterned structures for multiplexing in biochips. Issue 73 (28th September 2017) - Dias, T. M.; Fernandes, E.; Cardoso, S.; Monteiro, G.; Freitas, P. P.
Abstract : Correction for 'One-step trapping of droplets and surface functionalization of sensors using gold-patterned structures for multiplexing in biochips' by T. M. Dias et al., RSC Adv., 2017, 7, 43273–43282.